ANALISIS PENAWARAN TENAGA KERJA WANITA MENIKAH DAN FAKTOR YANG MEMPENGARUHINYA DI KABUPATEN BREBES - Nadia Maharani Putri; Evi Yulia Purwanti (Universitas Diponegoro, 2012)
ABSTRACT Nowadays, a lot of married women was entered the labor market, this condition makes the married women has a big role in household economy and in development too. And many research was held to explore the potency of married women workers. This research is purposed to analyze the factors which can influence the labor supply of married women in Kabupaten Brebes. Data analytical in this research used Ordinary Least Square (OLS) method, with labor supply of married women in the dependent variable and the six independent variables are wage/ income married women, husband’s income, age, education, amount of toddler, and household expenditure. This research used primary data (interviewing and question sheets) to 100 respondents and secondary data. The results of this research shows the average of timework of married women is 261,28 hours in a week, and the dominant variable is amount of toddler. The t-test shows the variable wage/ income, husband’s income, amount of toddler and household expenditure is significantly affect to the labor supply of married women. And then, variable age and education is not significantly affect to the labor supply of married women.